Faktor Pengaruh Kualitas Pelayanan, Harga dan Kepuasan Turis Di Tanjung Lesung Provinsi Banten - Soehardi, Soehardi (Jurnal Kajian Ilmiah, 2021)
The purpose of this study was to analyze the factors of service quality, price and satisfaction of foreign and domestic tourists in the Special Economic Zone of Tanjung Lesung, Pandeglang Municipality, Banten Province. The population consisted of foreign and domestic tourists visiting Tanjung Lesung, while the sample used was accidental sampling, with a total of 140 respondents. The quantitative research method used in this study was the analysis of validity, reliability, t test, F test and R square tests with SPSS software. Service quality has a significant effect on tourist satisfaction in the Special Economic Zone of Tanjung Lesung, Pandeglang Municipality, Banten Province. Tourist attractiveness as the main indicator of service quality compared to other indicators such as destination facilities and accessibility to tourist destinations. Price has a significant effect on tourist satisfaction in the Special Economic Zone of Tanjung Lesung, Pandeglang Municipality, Banten Province. Hotel room prices are the main indicator compared to other indicators such as food and beverages prices, sports equipment rental prices and professional fees for tour guides. Service quality and price together have a significant effect on tourist satisfaction in the Special Economic Zone of Tanjung Lesung, Pandeglang Municipality, Banten Province. The natural scenery of the white sand beach resort with a background of sea waves and the Child of Mount Krakatau is the main indicator of tourist satisfaction compared to other indicators such as several tourist visits, security and safety as well as cleanliness and hygiene.